Immigrants and employer-provided training - Alan Barrett; Seamus McGuinness; Martin O'Brien; Philip J. O'Connell (Institute for the Study of Labor (IZA), 2009)
Much has been written about the labour market outcomes for immigrants in their host countries, particularly with regard to earnings, employment and occupational attainment. However, much less attention has been paid to the question of whether immigrants are as likely to receive employer-provided training relative to comparable natives. As such training should be crucial in determining the labour market success of immigrants in the long run it is a critically important question. Using data from a large scale survey of employees in Ireland, we find that immigrants are less likely to receive training from employers, with immigrants from the New Member States of the EU experiencing a particular disadvantage. The immigrant training disadvantage arises in part from a failure on the part of immigrants to get employed by training-oriented firms. However, they also experience a training disadvantage relative to natives within firms where less training is provided.
urn:nbn:de:101:1-200910141058
Keywords: J24; J61; 330; Immigrants; employer-provided training; Ireland; Migranten; Ausländische Arbeitskräfte; Betriebliche Bildungsarbeit; Arbeitsmarktdiskriminierung; Irland